Fisherman Insurance to Increase The Social Welfare of Fishers - Sari, Indrya; Arief, Andi Adri; Amri, Andi; Fachry, Mardiana E.; Wahid, Abdul (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
The purpose of this study was to determine the active role of the Department of Marine Affairs and Fisheries of Takalar Regency, in supporting the process of the occurrence of Fisherman's Insurance that has been implemented by the central government, and to find out what factors hinder and support fishermen in obtaining Fisherman's Insurance cards. As for the determination of respondents using the Snowball technique or known as a snowball. Selected informants based on the criteria for receiving fisherman insurance cards as many as 25 informants as primary data sources. Data collection techniques are observation, distribution of questionnaires and interviews. This research was carried out in Sampulungan Village, Galesong District, Takalar Regency in March-May 2021. From the results of the research the socialization process planned and carried out by the Marine and Fisheries Service assisted by village officials was very effective in encouraging the enthusiasm of fishermen to obtain information and become insurance members fishermen, the supporting factors for implementing fisherman insurance consist of; High commitment from DKP Takalar Regency in realizing fishermen's insurance, enthusiasm of fishermen in obtaining information and being participants in fisherman insurance from the government, as well as high support from the village government in socializing and implementing fisherman insurance in Sampulungan Village. While the inhibiting factor is that there are still many fishermen who do not understand well the importance of being a member of fishermen's insurance; The existence of administrative data collection that has not been completed, including multiple lists, as well as the issue of validity of the fisherman's insurance card, which is only valid for one year, is considered short for fishermen.